A Study on Teaching Model of Application Flipped Teaching in College English - Liang, Binbin (Pacific International Journal, 2022)
Driven by the strategy of education power and the integration of Internet, our country pays more and more attention to the high-quality development of education industry. In order to meet the individual learning needs of students, we need to fully mobilize multi-educational resources, explore new educational models, and form a targeted and adaptive education system. In college English teaching, in order to help students improve their English learning results and English application ability, teachers have gradually changed the traditional teaching mode and effectively used the flipped classroom teaching mode, optimizing the links of classroom setting, stressing the students' subjective status in the classroom, actively communicating with students, guiding students to gradually change their passive thinking of English learning, through the adjustment of teaching contents and elements, to provide students with better English learning experience, so that students in English learning more infectious. After the implementation of the flipped classroom teaching model, the college English teaching model has also been increased, and the teachers can effectively use the group cooperative learning method to make students communicate with each other through good interaction, in the mastery of more English knowledge, but also for students to create a good English learning environment.